THE STUDENTS’ WRITING SKILL OF DISCUSSION TEXT AT XII GRADE OF MAN 1 INDRAGIRI HILIR - Maylisha SY; Edi Ardian; Samsul Amri (Program Studi Pendidikan Bahasa Inggris, 2019)
The purpose of this research is to know students’ writing skill of discussion text. The design of this research was descriptive quantitative research. To reach the purpose above, the researcher was distributing test to twelfth Grade students of XII Agama 1 of MAN 1 Indragiri Hilir. The amount of them is 20 students. After collecting the data, the researcher found that their writing skill of discussion text was good. It was proven by their mean score that is 74.1. It can be concluded that students have had good skills to write discussion text. The researcher assumed that this good result can be because the students had been able to understand what the teacher explain during the teaching and learning process and they also read many texts in the library or the internet.